"SNAPPE-II (SCORE FOR NEONATAL ACUTE PHYSIOLOGY WITH PERINATAL EXTENSION) AS A PREDICTOR OF MORTALITY IN NICU." - Dr.H.S.NIRANJAN; Dr.A.S.JAGADISH; Dr.SREEHARSHA; Dr.NAVEEN BENAKAPPA (International Journal of Pharma and Bio Sciences, 2016)
The assessment of severity of illness with scoring system has been used to predict neonatal mortality in neonatal intensive care unit (NICU). Prospective study was conducted at tertiary care NICU between January 2008 to August 2009 to determine the validity of SNAPPE-II score in predicting the outcome in terms of mortality and duration of hospital stay. 248 newborns were enrolled in the study of which 34.2% were preterm, 61.2% were term and 4.4% were post-term .The crude NICU mortality rate was 15.7%.Higher SNAPPE- II scores correlated well with the outcome in terms of mortality. Among expired babies mean SNAPPE- II score was 45.7+/-18.689 compared to those among survived 21.04+/-15.418 which was statistically significant. Sensitivity, Specificity, Negative predictive value and Positive predictive value of SNAPPE-II score in predicting mortality were 76.9%, 87.1%, 52.6% and 95.3% respectively. For SNAPPE -II, ROC curve showed a cut off value of 37. Of the sample, 30 babies with a score of more than 37 expired while only 9 expired when the score was less than 37.SNAPPE- II is a useful tool in predicting illness severity in terms of mortality and morbidity in NICUs.